Identification of microfungi isolated from Belian fruits - Md Isa, Siti Fatimah; Mohd Zainudin, Nur Ain Izzati; Yong, Christina Seok Yien; Go, Rusea (Universiti Putra Malaysia Press, 2019)
Belian tree (Eusideroxylon zwageri Teijsm. & Binn.) is one of the highly demanded commercial timber tree indigenous to the Southeast Asian region. The tree is threatened with over exploitation; habitat destruction and slow regeneration. While vascular plants are known as major reservoirs of fungi species, there have been no studies to identify the microfungi isolated from fruits of this endemic tree. By using internal transcribed spacers (ITS) sequence analysis, five genera were isolated and identified as Annulohypoxylon, Daldinia, Hypoxylon, Lasiodiplodia and Trichoderma. This result will be primarily used as baseline data for further investigations on microfungi diversity associated with Belian tree.